Acquired Thrombophilic Hypercoagulable States Seen in Patients with Liver Cirrhosis: A Single Center Study - Sana Shabbir, Quratulain Mehmood, Hafiz Muhammad Ali Hasnain, Muhammad Saad, Saima Rasheed, Muhammad Faisal Javaid (Pakistan Journal of Medical & Health Sciences, 2022)
Among the common hemostatic issues of the patients of liver cirrhosis, deep venous thrombosis, pulmonary embolism, and intrahepatic thrombus development are more often ignored. With an estimated frequency ranging from 0.6 to 26 percent, portal venous thrombosis is another potentially dangerous consequence of liver cirrhosis. Objectives: To determine the frequency of various acquired thrombophilic / hypercoagulable states seen in patients with liver cirrhosis. Study design: Descriptive, cross sectional. Settings: Department of Medicine, Allied Hospital, Faisalabad Study duration: 30th June 2019 to 29th December 2019 Materials & Methods: Cirrhosis cases ranging in age from 25 to 75 years old and of both genders were included in the study. Patients with HCC, heritable thrombophilias such as the Factor V leiden mutation, congenital budd chiari, and cholestatic liver disorders such as primary biliary cirrhosis (PBC) and primary sclerosing cholangitis were also eliminated. To assess for hepatic decompensation, ultrasonography, LFTs, and other baseline procedures were performed. Doppler USG was performed in each case with the assistance of the Radiology Department of Allied Hospital Faisalabad to assess for DVT, Budd-Chiari syndrome, and Portal venous thrombosis. Results: Mean age of the patients enrolled was 52.08 ± 10.47 years. Among these 840 patients, 461 (54.88%) were male and 379 (45.12%) were females (ratio 1.2 : 1). Mean AST levels were 77.49 ± 8.93 units/liter. Mean ALT levels were 88.51 ± 9.17 units/liter. Mean total bilirubin levels were 8.33 ± 1.65 mg/dl. Frequency of various acquired thrombophilic / hypercoagulable states seen in patients with liver cirrhosis were as follows; portal vein thrombosis in 136 (16.19%) patients, budd chiari syndrome in 102 (12.14%), deep vein thrombosis in 96 (11.43%) and pulmonary embolism in 108 (12.86%) patients. Conclusion: This study concluded that frequency of various acquired thrombophilic / hypercoagulable states seen in patients with liver cirrhosis is quite high.